MEKANISME DAN PERLAKUAN AKUNTANSI IJARAH MUNTAHIYA BITTAMLIK PADA BMT SIDOGIRI - Adawiyah, Lailatul; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is aimed to find out the IjarahMuntahiyaBittamlikfinancing mechanism (IMBT) and the accountingtreatment in BMT UGT Sidogiri as one of the Islmaic Financial Institutions which has products based on theIMBT agreement and to analyze its compatibility with the SFAS 107, âAccounting of Ijarahâ. The result of theresearch shows that the implementation of this IMBT transaction, in general, is compatible with some issuewhich are regulated in that provision, even though there are some issues which have not compatible with theSFAS 107. the incompatibility is in the regulation of maintenance expenses which has been carried out by tenant(mustaâjir) whereas these expenses have to be borne by the owner (muâjir). The provision of transfer ofownership has been offered by using options which have been justified by the SFAS 107, i.e. Grant which has tobe carried out at the Fatwah of National Sharia Board-Indonesian Council of Ulama, the taâziris allowed to beconducted in order to make the customers more discipline in carrying out their liabilities, taâziris the sanction inthe form of fine of sum of money in which the agreement is signed, but this is not carried out the BMT. Based onthis findings, it can be concluded that the accounting principles of BMT UGT SidogiriSepanjang branch has notcompatible with the SFAS 107, and there is an incompatibility whit the provision of the Fatwah of NationalSharia Board-Indonesian Council of Ulama in the imposition of fine.Keywords: Ijarah muntahiya bittamlik, baitul maal wattamwil, SFAS No. 107.